2010
DOI: 10.1021/la100525h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Eu3+ Emission in Aqueous Phosphotungstate Colloidal Systems: Stabilization of Polyoxometalate Nanostructures

Abstract: Luminescent Eu(3+)-containing polyphosphate-tungstate aqueous colloidal systems were prepared and studied as a function of the relative polyphosphate-tungstate content. In polyphosphate-rich solutions, Eu(3+) ions occupy cagelike sites composed of phosphate groups from the metaphosphate chains. In these sites, an average number of 0.5 water molecule coordinates to an Eu(3+) ion and the (5)D(0) emission quantum efficiency is 0.22. Tungstate addition leads to important modifications in neighboring Eu(3+) leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…6A, right). The blue broad band with a maximum at about 455 nm should be caused by the O-W charge transfer, and the other sharp lines centered at 581, 595 and 615 nm are the characteristic transitions of Eu 3+ , which can be ascribed to the 5 D 0 → 7 F J (J = 0, 1, 2) transitions of the Eu 3+ ions, respectively [43][44][45][46]. On the basis of the above results, it is clear that the blue emission of WO 4 2− groups and red emission of the doped Eu 3+ occur simultaneously and yield a white light emission.…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…6A, right). The blue broad band with a maximum at about 455 nm should be caused by the O-W charge transfer, and the other sharp lines centered at 581, 595 and 615 nm are the characteristic transitions of Eu 3+ , which can be ascribed to the 5 D 0 → 7 F J (J = 0, 1, 2) transitions of the Eu 3+ ions, respectively [43][44][45][46]. On the basis of the above results, it is clear that the blue emission of WO 4 2− groups and red emission of the doped Eu 3+ occur simultaneously and yield a white light emission.…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…Ribeiro et al [53] have reported the synthesis of europium sodium-phosphate-tungstate colloidal systems in which the Eu 3 þ ions occupy cagelike sites composed of phosphate groups from the metaphosphate chains. The tungstate addition has led to the formation of W-rich nanoparticles (5-10 nm in diameter) and removal of water molecules from the first coordination sphere of Eu 3 þ .…”
Section: Nanoparticles Nanorods and Sol-gel Processmentioning
confidence: 99%
“…Among the well-known lanthanide polyoxometalates, the decatungstoeuropate anion ([EuW 10 O 39 ] 9– ) exhibits outstanding luminescence performance. In its structure, the Eu 3+ ions are coordinated by two [W 5 O 18 ] 6– ligands, as a result of the efficient energy transfer from O → W ligand-to-metal charge transfer (LMCT) states to the Eu 3+ ions’ excited states. However, the poor processing capacity of polyoxometalates usually limits their practical applications. One of the most effective methods is the introduction of suitable hosts to improve the processing capacity of polyoxometalates, such as polymers, zeolites, and ionic liquids. Among the numerous hosts, the polymers with a high film-forming ability have captured great attentions, and the resulting film with flexible property has a potential application as a paper medium to replace conventional paper.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism Analysis. It is known that Eu-containing polyoxometalates exhibit strong red emission due to the intramolecular energy transfer,[31][32][33]51 which includes two steps. First, photoexcitation into the O → W LMCT would cause the hopping of the d 1 electron and is accompanied by the released energy via the deactivated recombination between d 1 electrons and holes.…”
mentioning
confidence: 99%